Adsorption and reaction properties of SnBEA, ZrBEA and H-BEA for the formation of p-xylene from DMF and ethylene. Issue 14 (27th April 2016) - Yu, Jingye; Zhu, Shiyu; Dauenhauer, Paul J.; Cho, Hong Je; Fan, Wei; Gorte, R. J.
Abstract : The adsorption and reaction properties of H-BEA, SnBEA, ZrBEA and siliceous BEA were examined to understand the reaction of 2, 5-dimethylfuran (DMF) with ethylene to form p -xylene. Abstract : The adsorption and reaction properties of H-BEA, SnBEA, ZrBEA and siliceous BEA were examined to understand the reaction of 2, 5-dimethylfuran (DMF) with ethylene to form p -xylene. Temperature-programmed desorption (TPD) of diethyl ether, DMF, 2, 5-hexanedione and p -xylene on each of the zeolites demonstrated that the Brønsted sites in H-BEA are more reactive than the Lewis sites in SnBEA and ZrBEA and tend to promote the oligomerization of DMF and 2, 5-hexanedione, even at 295 K; however, the adsorbed 2, 5-hexanedione is converted to DMF at both Lewis- and Brønsted-acid sites. H-BEA, SnBEA and ZrBEA all catalyzed the reaction to p -xylene with high selectivity in a continuous-flow reactor, with all three catalysts showing rates that were first order in both DMF and ethylene. H-BEA was found to deactivate rapidly due to coking, while ZrBEA and SnBEA were both stable. The implications of these results for practical applications are discussed.